Partners in the Transfer of Learning: A Qualitative Study of Workplace Literacy Programs - Maurice C. Taylor (Adult Education Research Conference, 2000)
This study investigated the common types of transfer strategies used by the key stakeholders in 11 Canadian workplace education programs. Results indicated that the Role Time Model was a useful classification system: to understand the dimensions of a transfer partnership; to document the transfer of learning strategies and to identify the barriers influencing the transfer of learning.